Pendidikan ekonomi di pondok pesantren Hidayatut Thullab Kabupaten Trenggalek - Ayuniva Putri; Wahjoedi Wahjoedi; Agung Haryono (Universitas Negeri Malang, 2017)
Economic problems are complex problems that can not be separated from human life. The best way to solve economic problems in Indonesia is to shape human capital through investment in education. Basically boarding school education is the original education system of Indonesia or known as Indigenious. The existence of traditional pesantren or pondok pesantren salaf become the attraction to be studied because in the middle of the modernization of education changes there are still pondok pesantren that survive with salafiyah system. If in formal education, economic education becomes a curriculum that must be studied by the students. However, in boarding schools salaf does not include economic education as a compulsory curriculum. This is a challenge for students of pondok pesantren to study themselves and apply economic activities in daily life. This study aims to describe the process of economic education in Pondok Pesantren Hidayatut Thullab Trenggalek District. The method used is qualitative approach with case study research type. The results of this study indicate that the economic education process that exists in Pondok Pesantren Hidayatut Thullab not given formally written in the curriculum, but given to the santri implicitly through learning yellow books. Given the insights derived from these books the santri can apply them through attitude changes and the formation of behavior about economic activity. Giving opportunities to work to make santri can directly practice their economic behavior. Pondok environment is very influential on economic education obtained by the students at Pondok Pesantren Hidayatut Thullab. The cottage environment in question consists of huts, mosques, classical Islamic teaching books, Santri, Kyai, communities around the lodge as well as the environment where the students work. Based on the results of the study is suggested for Pondok Pesantren Hidayatut Thullab provide insight and expertise to the students from inside the cottage in order to work and conduct economic activities more leverage. KeywordsEducation, Economic Education, Pondok Pesantren. http://dx.doi.org/10.17977/um022v2i22017p104